Analysis of vascular surgery for kidney transplantation: About 50 observations - Balboa, Oscar; Voelker, Ricardo; Tchekmedyian, Vartan; Pereira Bonasso, José (Cirugía del Uruguay, 1986)
Study of vascular surgery in connection with renal transplantation, on the basis of 50 cases observad. Owing to the various presentallons of the renal pedicte it was necessary to employ a large range of different procedures that led to the use of practically every possible variation in this field. There is only one complication directly associated with vascular surgery: acute arterial occlusion caused by atheroma deposits being drawn and embolized. Complications are enumerated, pointing out that results as a whole in one year are comparable to those obtained in other place.